HUBUNGAN TUNGAU DEBU RUMAH TERHADAP ANGKA KEJADIAN RINITIS ALERGI YANG BEROBAT DI POLI THT RSUD BANGLI TAHUN 2019 - Kairavini, Ardyatri; Ariani, Trisna; utami, sukdriani; Hikmallah, Nurman (JURNAL KEDOKTERAN, 2020)
Background: Rhinitis Allergic is an inflammatory process in the nasal mucosa caused by type I hypersensitivity reactions that are triggered by certain allergens. The prevalence of rhinitis allergic in Indonesia is estimated to range between 10- 20% and is constantly increasing. The average Onset age of Rhinitis Allergic is 8- 11 years old and 80% of rhinitis allergic develops at the age of 20 years old. Usually rhinitis allergic occurs at a young age. Rhinitis Allergic can be triggered by several types of aeroallergens, one of which is house dust mites. Lopo C research mentioned that most allergens cause allergic rhinitis are house dust mites that is equal to (75.6%). Objective: To determine the correlation of house dust mites to the incidence of rhinitis allergic being treated at the ENT Polyclinic in Bangli Regional Hospital in 2019. Method: This study was an observational study with a cross sectional design. Samples were taken based on primary and secondary data using non-probability sampling techniques by purposive sampling. The samples used in this study were 143 samples of rhinitis patients. Data analysis using Chi Square. Results: The results obtained from the Chi Square test did not have a significant correlation of house dust mites and the number of incidence of allergic rhinitis is p-value 0.060 (p> 0.05). Conclusion: There is no significant correlation of household dust mites and the incidence of rhinitis allergic in the ent polyclinic of Bangli hospital in 2019.